2018
DOI: 10.1007/s13197-018-3094-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Argel (Solenostemma argel) leaf extract on quality attributes of chicken meatballs during cold storage

Abstract: This study aimed to evaluate the antioxidant activity of Argel leaf water extract (ALWE) and its effect at different concentrations (0, 5, 10, and 20 mg/100 mL) on the antioxidant, antimicrobial, physicochemical, and sensory attributes of chicken meatballs during cold storage. ALWE contained substantial quantities of total phenolic content (TPC), anthocyanin, and exhibited high DPPH scavenging activity. ALWE incorporation in chicken meatballs had a varying effect on the chemical composition and sensory attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…The lipid oxidation was reduced by the inclusion of CP in the beef burgers due to the phenolics present in the CP. This is in agreement with findings observed in meat patties containing clove extract [ 25 , 26 , 27 ], argel leaf water extract [ 12 ], baobab seed extract [ 16 ], Acacia nilotica seed extracts [ 14 ], and Moringa seed powder [ 9 ]. The presence of antioxidant compounds in the treated burgers is expected to control the oxidative processes in the beef burgers during the cold-storage period.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The lipid oxidation was reduced by the inclusion of CP in the beef burgers due to the phenolics present in the CP. This is in agreement with findings observed in meat patties containing clove extract [ 25 , 26 , 27 ], argel leaf water extract [ 12 ], baobab seed extract [ 16 ], Acacia nilotica seed extracts [ 14 ], and Moringa seed powder [ 9 ]. The presence of antioxidant compounds in the treated burgers is expected to control the oxidative processes in the beef burgers during the cold-storage period.…”
Section: Resultssupporting
confidence: 91%
“…Plant materials, such as spices and herbs, are rich in bioactive compounds, such as phenolics and flavonoids, which exhibit antioxidant and antibacterial properties [ 6 ]. For example, antioxidants derived from plants, such as Moringa oleifera seed powder [ 9 ], olive cake powder [ 1 ], pistachio seed hull extract [ 10 ], Argel leaf powder and extract [ 11 , 12 ], Acacia nilotica fruit and seed extracts [ 13 , 14 ], Ephedra alata extract [ 15 ], baobab ( Adansonia digitata ) seed extract [ 16 ], red pitaya extract [ 17 ]), and Colombian berry ( Vaccinium meridionale Sw.) extracts [ 18 ], have been found to maintain the quality properties and enhance the storage stability of meat products.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of TBARS contents might be put down to the denatured structure of the muscles during the storage ( Cao et al, 2013 ). These appreciable results showed that LBP presented stable in lipid oxidation of meatballs compared with the control ( Al-Juhaimi et al, 2018 ). However, the TBARS contents decreased in the 0.03% LBP-treated group from 3 to 6 weeks and in the control from 9 to 12 weeks (p<0.05).…”
Section: Resultsmentioning
confidence: 80%
“…It is the only known species in the genus, Solenostemma, subfamily Asclepiadoideae, and family, Apocynaceae. In traditional herbal medicine, S. argel plants are used to enhance immunity, support kidney and liver functions, and to treat anti-urinary tract infections; when used as an anti-rheumatic agent, it greatly increased all histopathological parameters (Al-Juhaimi et al, 2018;El-Shiekh et al, 2021), such as flavones (kaempferol, isorhamnetin, naringenin, and quercetin), phenols (trans-cinnamic acid, gallic acid, caffeic acid, and syringic acid), polyphenols (resveratrol and catechol), glycosylated flavonoids (apigenin-7-glucoside and quercetin-3rutinoside), pregnane, pregnenes, β-sitosterol, and β-carotene (Plaza et al, 2005;Ounaissia et al, 2016).…”
Section: Introductionmentioning
confidence: 99%